Copper nanowire coated carbon fibers as efficient substrates for detecting designer drugs using SERS - Halouzka, Vladimir; Halouzkova, Barbora; Jirovsky, David; Hemzal, Dusan; Ondra, Peter; Siranidi, Eirini; Kontos, Athanassios G; Falaras, Polycarpos; Hrbac, Jan (Talanta, 2017)
Miniature Surface Enhanced Raman Scattering (SERS) sensors were fabricated by coating the carbon fiber microelectrodes with copper nanowires. The coating procedure, based on anodizing the copper wire in ultrapure water followed by cathodic deposition of the anode-derived material onto carbon fiber electrodes, provides a "clean" copper nanowire network. The developed miniature (10µm in diameter and 2mm in length) and nanoscopically rough SERS substrates are applicable in drug sensing, as shown by the detection and resolving of a range of seized designer drugs in trace amounts (microliter volumes of 10-10-10-12M solutions). The copper nanowire modified carbon microfiber substrates could also find further applications in biomedical and environmental sensing.
Keywords: Designer drugs; karbonové vlákno; Spectrum Analysis, Raman; biosenzitivní techniky; Copper; Carbon Fiber; uhlík; Copper nanowire; povrchové vlastnosti; měď; Biosensing Techniques; Carbon; SERS substrate; Surface Properties; nanodráty; Nanowires; Electrodeposition; Designer Drugs; elektrody; nové syntetické drogy; Carbon fiber; SERS; Electrodes; Ramanova spektroskopie